A General Strategy for Macrotheranostic Prodrug Activation: Synergy between the Acidic Tumor Microenvironment and Bioorthogonal Chemistry. Issue 18 (6th March 2020) - Dong, Yansong; Tu, Yalan; Wang, Kewei; Xu, Congfei; Yuan, Youyong; Wang, Jun
Abstract: Prodrugs activated by endogenous stimuli face the problem of tumor heterogeneity. Bioorthogonal prodrug activation that utilizes an exogenous click reaction has the potential to solve this problem, but most of the strategies currently used rely on the presence of endogenous receptors or overexpressed enzymes. We herein integrate the acidic, extracellular microenvironment of a tumor and a click reaction as a general strategy for prodrug activation. This was achieved by using a tumor pH‐responsive polymer containing tetrazine groups, which formed unreactive micelles in the blood but disassembled in response to tumor pH. The vinyl ether group on the macrotheranostic prodrug (CyPVE) is activated by the tetrazine groups, which was confirmed by tumor‐specific fluorescence activation and phototoxicity restoration. Therefore, the bioorthogonal reactions in the context of the ubiquitous acidic tumor microenvironment can provide a general strategy for bioorthogonal prodrug activation. Abstract : Bioorthogonal prodrug activation : A strategy for prodrug activation was developed that uses the acidic tumor microenvironment and a bioorthogonal click reaction. A tetrazine‐functionalized pH‐sensitive polymer micelle disassembles in the acidic tumor microenvironment, exposing the tetrazine groups that activate the prodrug. Prodrug activation is confirmed by a NIR fluorescence signal and the restoration of phototoxicity in the tumor.